TEACHER STRATEGIES IN RESPONDING TO RELIGIOUS INTOLERANCE: A Case Study in Indonesian Elementary School - Sofiyyah, Sofiyyah; Fa'atin, Salmah (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
Purpose: This study aims to analyze teachers' strategies in responding to religious intolerance among students at SD Negeri 01 Jati Kulon. Method: The study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. Result: Teachers apply three main strategies, namely (1) preventive strategies based on internalization of values, (2) curative strategies based on restorative dialogue, and (3) social reinforcement strategies through school-parent-community partnerships. These three strategies are effective in building empathetic awareness and interfaith acceptance in the school environment. Conclusion: This study contributes by providing an in-depth qualitative analysis of classroom-level responses to religious intolerance, an area that remains underexplored in elementary education research. Adaptive, collaborative, and contextual teacher strategies are key to fostering a culture of tolerance in elementary schools. The researchers recommended the importance of religious digital literacy for teachers and parents, as well as the development of a tolerance education model based on local wisdom in elementary schools.